A Psychoanalytic Analysis of Selected Short Stories of Manto - Khan, Anwar Ullah; Ali, Anwar (Makhz (Research Journal), 2024)
This research paper explores the representation of Post-Traumatic Stress Disorder (PTSD) in selected short stories of Saadat Hasan Manto, a prominent writer of colonial and post-colonial South Asian literature. PTSD, a key concept in Sigmund Freud’s psychoanalysis, emerges in Manto’s narratives as a profound psychological condition shaped by the violence, displacement, and socio-political turmoil of partition-era India. His characters often experience severe psychological distress, reflecting the broader societal trauma of historical events and illustrating the deep connection between individual suffering and collective memory. Using a psychoanalytic framework, this study examines how PTSD and hysteria—another significant Freudian concept—manifest in Manto’s works as socio-psychological disorders that contribute to various social issues, including alienation, moral decline, and violence. Manto’s realistic and unfiltered storytelling provides a compelling critique of the human psyche under extreme trauma, portraying fractured identities and mental instability as consequences of larger socio-political crises. By analyzing Manto’s portrayal of PTSD and hysteria, this study contributes to the understanding of psychological disorders in literature and provides insights into the relationship between trauma and narrative. This research also lays the groundwork for further scholarly exploration of other social and psychological conditions in Manto’s writings, emphasizing the relevance of psychoanalysis in literary studies and highlighting the intersection of literature, history, and mental health in the South Asian context.